Factors Predicting Operation of Local Health Security Fundsin Chachoengsao Province - Intarauthok, Jongjit; Kriengkaisakda, Warakorn (Journal of Health Science of Thailand, 2017)
The objective of this study was to identify factors predicting the operation of local health security funds (LHSFs) in Chachoengsao province. The samples were personnel of local administrative organizations or municipalities working in all 108 LHSFs of the province, one person from each fund; and 108 local health personnel whose work was related to the local LHSF operation, one from each locality. Altogether 216 samples were purposively recruited. Data collection was conducted by using a set of questionnaire developed by the authors, of which the reliability level as measured by Cronbach’s alpha coefficient was 0.791 for knowledge of the LHSF, 0.862 for attitude on the operation, 0.914 for social support, and 0.942 for local political factors. Statistics used for data analysis included frequency, percentages, means, standard deviations, and multiple regression analysis. It was found that the overall performance of health personnel in the operation of the local health security funds in the province was at a high level with the mean value of 3.72. There was a high level of knowledge on LHSF (77.76%), moderate level of attitude (56.02%), moderate level of social support (53.70%), and high level of local political influence (66.21%). Thus, facots predicting the outcomes of the operations of LHSFs in Chachoengsao province included social support for the funds, local political factors, knowledge on the fund, and attitudes of personnel. These facotrs were found to be significantly influential on the outcomes of the LHSFs by 42.60% (p<0.05).